A novel open‐source software‐based high‐precision workflow for target definition in cardiac radioablation. (21st July 2020) - Hohmann, Stephan; Henkenberens, Christoph; Zormpas, Christos; Christiansen, Hans; Bauersachs, Johann; Duncker, David; Veltmann, Christian
Abstract: Introduction: Noninvasive ablative radiotherapy of cardiac arrhythmias (stereotactic ablative body radiation) has shown promising initial results. Precise targeting of the arrhythmogenic substrate is paramount to limit adverse effects to healthy myocardium, organs at risk, and cardiac implantable electronic devices. Using electroanatomic maps for treatment planning is technically challenging. Methods and Results: Using the free open‐source 3D Slicer software platform we established a workflow for high‐precision target definition based on electroanatomic maps. An import plug‐in for 3D Slicer has been designed that reads electroanatomic maps generated with three mapping systems in widespread clinical use. Using our proposed workflow in a real‐world patient case we were able to align the map to the computed tomography (CT) with a mean distance of 3.1 mm. Thus, points defined on the map were translated into CT space with high accuracy and a radiotherapy treatment volume was defined in CT space based on these map‐derived points. Conclusion: We describe a novel high‐precision target definition method for stereotactic ablation of cardiac arrhythmias. Multimodal integration of the electroanatomic map with the planning CT allows for highly accurate localization of previously identified electrophysiological features in CT space. It remains to be shown whether this novel planning workflow leads to superior ablation outcomes when compared with other approaches.